On the relationship between income, fertility rates and the state of democracy in society - Hutzler, Stefan; Richmond, Peter (My University, 2016)
Empirical data for 145 countries shows a strong correlation between the gross national income per capita and the political form of their governance, as specified by the so-called democracy index. We interpret this relationship in analogy to phase transitions between different states of matter, using concepts of statistical physics. Fertility rates play the role of binding energy in solid state physics.
PUBLISHED
Keywords: International Development; International Integration; Physics; sociophysics